Assessing Availability in Wireless Visual Sensor Networks Based on Targets’ Perimeters Coverage - Daniel G. Costa; Cristian Duran-Faundez (Journal of Electrical and Computer Engineering)
Availability in wireless visual sensor networks is a major design issue that is directly related to applications monitoring quality. For targets monitoring, visual sensors may be deployed to cover most or all of targets, and monitoring quality may be focused on how well a set of targets are being covered. However, targets may have different dimensions and it is expected that large targets may be only partially viewed by source nodes, which may affect coverage quality and lead to a state of unavailability. In this context, this article analyzes the effect of target’s size on effective coverage in wireless visual sensor networks. A new coverage metric, the Effective Target Viewing (ETV), is proposed to measure monitoring quality over a set of targets, which is exploited as a fundamental parameter for availability assessment. Results show that ETV can be used as a practical coverage metric when assessing availability in wireless visual sensor networks.